Understanding Repurchase Intention in Digital Consumption: The Role of Perceived Benefits, Gamification, Online Persuasion, and Consumer Attitude - Cindy Theodora; Barkah; Harry Setiawan; Ramadania; Bintoro Bagus Purmono (Journal of Educational Management Research, 2026)
This study aims to examine the influence of perceived benefits, gamification, and online persuasion on repurchase intention, with consumer attitude serving as a mediating variable. A quantitative survey approach was employed by collecting data from 294 respondents who had prior experience purchasing from digital-based coffee shop services. The sampling technique used purposive sampling, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that perceived benefits, gamification, and online persuasion have positive and significant effects on both consumer attitude and repurchase intention. Furthermore, consumer attitude significantly mediates the relationship between these three variables and repurchase intention, indicating that consumers’ evaluative responses play a crucial role in translating digital marketing stimuli into repeat purchase behavior. These findings highlight the importance of enhancing interactive digital features, emphasizing both functional and emotional value, and developing culturally relevant online communication strategies. Such strategies can strengthen consumer attitudes, improve engagement with digital platforms, and ultimately encourage stronger repurchase intention among consumers in increasingly competitive digital service environments.